Variable-Structure Control Design of Switched Systems With an Application to a DC-DC Power Converter - Cardim, Rodrigo [UNESP]; Teixeira, Marcelo C. M. [UNESP]; Assuncao, Edvaldo [UNESP]; Covacic, Marcio Roberto (Institute of Electrical and Electronics Engineers (IEEE), 2009)
This paper is concerned with the design of state-feedback variable-structure controllers (VSCs) for a class of continuous-time switched plants. In particular, a new VSC design method based on Lyapunov-Metzler (LM) inequalities and the properties of strictly positive real (SPR) systems is suggested. The method is applied to the control of a dc-dc power converter: The performance of the resulting control system is superior to that afforded by a recently proposed alternative sliding-mode control technique. The definition of LM-SPR systems and its direct application to establish a procedure for designing the switching rule and VSC input are presented.
Keywords: DC-DC converters; linear matrix inequalities (LMIs); Lyapunov-Metzler (LM) inequalities; strictly positive real (SPR) systems; switched systems; variable-structure control